2016
DOI: 10.1111/bph.13365
|View full text |Cite
|
Sign up to set email alerts
|

Low free drug concentration prevents inhibition of F508del CFTR functional expression by the potentiator VX‐770 (ivacaftor)

Abstract: BACKGROUND AND PURPOSEThe most common cystic fibrosis (CF) mutation F508del inhibits the gating and surface expression of CFTR, a plasma membrane anion channel. Optimal pharmacotherapies will probably require both a 'potentiator' to increase channel open probability and a 'corrector' that improves folding and trafficking of the mutant protein and its stability at the cell surface. Interaction between CF drugs has been reported but remains poorly understood. EXPERIMENTAL APPROACHCF bronchial epithelial cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 31 publications
6
60
0
1
Order By: Relevance
“…Such inhibitory interactions are especially concerning given that LUMA only partially restores (11–15%) F508del-CFTR surface expression [13, 22, 23]. Various independent research groups have reported that IVA downregulates the restored F508del-CFTR whether it was modulated by LUMA or the investigational corrector VX-661 [14, 22, 23]. Matthes et al claimed that the inhibitory effects of IVA against the corrector function of LUMA only occurs at relatively high IVA concentrations (5–10μM, used in all of the reported cell culture studies) and that this inhibitory effect is unlikely to occur at the low (1.5–8.5 nM) free IVA concentrations achievable in vivo [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such inhibitory interactions are especially concerning given that LUMA only partially restores (11–15%) F508del-CFTR surface expression [13, 22, 23]. Various independent research groups have reported that IVA downregulates the restored F508del-CFTR whether it was modulated by LUMA or the investigational corrector VX-661 [14, 22, 23]. Matthes et al claimed that the inhibitory effects of IVA against the corrector function of LUMA only occurs at relatively high IVA concentrations (5–10μM, used in all of the reported cell culture studies) and that this inhibitory effect is unlikely to occur at the low (1.5–8.5 nM) free IVA concentrations achievable in vivo [14].…”
Section: Resultsmentioning
confidence: 99%
“…The annual cost per patient for both drugs is high ($259,000–$311,000 USD), and presently their manufacturer Vertex has a market monopoly as these are the only drugs on the market available for their indication [12]. The clinical efficacy of ORKAMBI versus the cost of therapy has been brought into question due to potential antagonistic drug-drug interactions between IVA and LUMA that potentially limit the clinical efficacy of ORKAMBI [13, 14]. Additional factors that may limit ORKAMBI’s clinical efficacy come from its less than ideal pharmacokinetic properties [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veit et al, 2014), a compound designed to correct the trafficking defects of the most common pathogenic mutation ΔF508 (Van Goor et al, 2011). Although this negative impact of VX-770 on the action of VX-809 may not be as severe when the VX-770 concentration is in the nanomolar range (Matthes et al, 2016), new CFTR potentiators with few drug-drug interactions seem warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Matthes et al [67] suggested that the inhibitory effects of the lumacaftor-ivacaftor combination therapy is due to high concentrations of free ivacaftor present in plasma, and that improving CFTR function would require lowering potentiator concentration and using more efficacious correctors. It was recently discovered that some other potentiators did not appear to markedly inhibit the correction of F508del [64, 68].…”
Section: Expert Commentarymentioning
confidence: 99%